2001
DOI: 10.1142/s0218625x01001427
|View full text |Cite
|
Sign up to set email alerts
|

RELAXATION OF Cu(100), (110) AND (111) SURFACES USING AB INITIO PSEUDOPOTENTIALS

Abstract: The geometries of the Cu(100), Cu(110) and Cu(111) surfaces are determined using ab initio pseudopotential calculations. Use of the Hellmann-Feynman theorem to calculate forces allows the determination of the equilibrium atomic positions with a small number of trial geometries. Our calculated results show that the surface relaxation of Cu(100) and Cu (110) surfaces are inward relaxations, while that of Cu(111) surface is slightly outward relaxation. Our results show that the forces, charge transfer and the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
1
5
1
Order By: Relevance
“…[35], but is in contrast to the PPPW calculations reported in Ref. [48], which found an expansion for the topmost interlayer spacing. Furthermore, our results are fully in accord with similar calculations performed by Da Silva et al [51] using the FP-LAPW method.…”
Section: Interlayer Spacing Relaxationscontrasting
confidence: 61%
See 1 more Smart Citation
“…[35], but is in contrast to the PPPW calculations reported in Ref. [48], which found an expansion for the topmost interlayer spacing. Furthermore, our results are fully in accord with similar calculations performed by Da Silva et al [51] using the FP-LAPW method.…”
Section: Interlayer Spacing Relaxationscontrasting
confidence: 61%
“…And theoretically, first-principles calculations also give an accurate description, see for example, Refs. [7,[34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53], where it has been found that the majority of transition metal surfaces show a contraction of the first interlayer spacing, i.e., the spacing between the two outermost layers is smaller than in the bulk terminated (unrelaxed) surface. An expansion of the outermost interlayer spacing has been reported, e.g., for Mg(0 0 0 1) [29,33,37,44,45], Al(1 1 1) [11,22,24,28,31,46], and Pt(1 1 1) [21,22,47,50].…”
Section: Introductionmentioning
confidence: 99%
“…Our results give −3.49% relaxation for Cu(1 1 0), in agreement with other theoretical data, which ranges from −3.7% to −9.3% [50,54,57,58]. The magnitude reported in this work is smaller than that of experimental and theoretical data reported in literature, but consistent with that by molecular dynamics calculations (−3.7%) [58].…”
Section: Oxygen-free Undoped Cu Surfacessupporting
confidence: 91%
“…In the case of the Cu(1 1 0) surface, the relaxation is normal inward relaxation and the magnitude is large compared to the others surface according to the concept that the close-packed surfaces such as (1 0 0) and (1 1 1) show smaller relaxations while the open (1 1 0) surface shows larger relaxation. The experimental results predicted a contraction for d 12 of about 9.0% [48,49] and an expansion for d 23 of about 2% [48][49][50]. The calculated slab relaxation was −0.18 Å (−3.5%) for the first layer of the surface, and +0.03 Å (2.3%) for the second layer.…”
Section: Oxygen-free Undoped Cu Surfacesmentioning
confidence: 88%
“…At present, slab model in ab initio calculations associated with surface and interface systems studies is one of the most usable approaches [3,4]. A slab model is a supercell that contains an atomic cluster with some atomic layers and a vacuum region (Fig.…”
mentioning
confidence: 99%